Validation of Monte Carlo multithreading TOpas 3.6 software in order to simulate the 6 MV Elekta Synergy MLCi2 platform linac - Krim, Deae-eddine; Rrhioua, Abdeslem; Zerfaoui, Mustapha; Bakari, Dikra; Hamal, Mohammed; Moukhlissi, Mohamed (Reports of practical oncology and radiotherapy, 2022)
Monte Carlo simulation is generally appreciated as an extraordinary technique to investigate particle physics processes and interactions in nuclear medicine and Radiation Therapy. The present task validates a new methodology of Monte Carlo simulation based on the Multithreading technique to reduce CPU time to simulate a 6 MV photon beam provided by the Elekta Synergy MLCi2 platform medical linear accelerator treatment head utilizing TOpas version 3.6 Monte Carlo software and the Slurm Marwan cluster. The simulation includes the linear accelerator (LINAC) major components. Calculations are performed for the photon beam with several treatment field sizes varying from 3 × 3 to 10 × 10 cm at a 100 cm of distance from the source to the surface of the IBA dosimetry water box. The simulation was wholly approved by comparison with experimental distributions. To evaluate simulation accuracy, gamma index formalism for (2%/2mm) and (3%/2mm) criteria, Distance To Agreement DTA, and the estimator standard error and are used. Good agreement between simulations and measurements was observed for depth doses and lateral dose profiles, respectively. The gamma index comparisons also highlighted this agreement; more than 97% of the points for all simulations satisfy the quality assurance criteria of (2%/2mm). Regarding calculation performance, the event processing speed is faster using Gate-[mp] compared to TOpas-[mt] mode when running the identical simulation code for both. Consequently, according to the achieved results, the proposed methodology shows the first validation of TOpas in radiotherapy linacs simulations and a reduction in calculation time, capping simulation accuracy as much as possible. For this reason, this software is recommended to be serviceable for Treatment Planning Systems (TPS) purposes.